Bark of passiflora edulis treatment stimulates antioxidant capacity, and reduces dyslipidemia and body fat in db/db mice - Panelli, Marielle Fernanda [UNESP]; Pierine, Damiana Tortolero [UNESP]; de Souza, Sérgio Luiz Borges [UNESP]; Ferron, Artur Júnio Togneri [UNESP]; Garcia, Jéssica Leite [UNESP]; Dos Santos, Klinsmann Carolo [UNESP]; Belin, Matheus Antônio Filiol [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Borguini, Milena Galhardo [UNESP]; Minatel, Igor Otávio [UNESP]; Cicogna, Antônio Carlos [UNESP]; Francisqueti, Fabiane Valentini [UNESP]; et al. (MDPI, 2018)
Obesity is considered an important risk factor for several disorders, such as diabetes mellitus, systemic arterial hypertension, dyslipidemia, and atherosclerosis, which are associated with inflammation and oxidative stress as a trigger factor. Passiflora edulis contains important bioactive compounds, such as phenolics, carotenoids, vitamin C, and polyamines in pulp, leaves, seeds, and bark. Aim: To evaluate the effect of bark of Passiflora edulis (BPe) on body composition, and metabolic and oxidative stress parameters in genetically obese mice. Methods: Obese male db/db mice (n = 14 animals) received normal feeds and water ad libitum for 8 weeks. Then, animals were randomly divided to continue either receiving standard chow (obese, n = 7 (OB)) or feed with standard chow plus bark Passiflora edulis (BPe) (obese + BPe, n = 7 (OB + BPe)) for 8 more weeks, totaling 16 weeks. BPe was added to chow (7 g of BPe/kg of chow corresponding to 1.5 g/kg of body weight). The parameters evaluated in animals included food and caloric intake, body weight, body fat, plasma glucose, triglycerides, and total cholesterol. Malondialdehyde and antioxidant capacity were evaluated in plasma and organs. Groups were compared by Student t-test, with p < 0.05. Results: BPe reduced visceral and subcutaneous fat deposit and adiposity index, cholesterol and triglyceride levels, ameliorated the antioxidant capacity, and reduced malondialdehyde (MDA) levels. Conclusion: the bark of Passiflora edulis was effective in improving body composition, and metabolic and antioxidant parameters in obese mice.
Keywords: Db/db mice; Obesity; Oxidative stress; Passiflora edulis